STORIES OF MOTHERS WITH INTELLECTUAL DISABILITY CHILDREN IN WEST SUMATERA, INDONESIA - Liza Merianti; Dona Amelia; Ade Srywayuni; Sari Afma Yuliane (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Children with intellectual disability are rejected not only by other individuals around them but also by their own family. Even though they need support from the mother to achieve accurate conformity. The form of mother social support can be in the form of emotional support, appreciation, instrumental and informative. However, the parents of Children with intellectual disability often refuse the presence of their children. The purpose of this study was to obtain qualitative data on the experience of mothers who have intellectually disabled children Methods: This study is a qualitative research conducted by interview using the semi-structured interview method. The participants were selected by using purposive sampling technique. The data were qualitative analyzed by employing Collaizi model. The participants in this study were 6 mothers who have children with intellectual disability Results: Participants have a positive perception about the educational needs of children with intellectual disability. However, due to financial issues, participants do not provide education for their intellectually disabled children. They mentioned that if their intellectually disabled children were properly, they would be able to take care of themselves and would no longer depend on others. Conclusion: In this study, the researchers found five themes of mothers’ stories with intellectual disability child in West Sumatera, Indonesia, including (1) their unawareness of their intellectually disabled children condition; (2) disappointment as the initial response knowing their children status; (3) anxiety and worry about their children future; (4) financial issues as a factor in obstructing education, and (5) religious worship as a source of strength. The results of this study can be used in nursing practice so that families can maintain the sources of strength to accept the fact that they have children with intellectual disabilityand that education is very important for children with intellectual disability. Keywords: Intellectual Disability, Education, Mothers’ Experience, Mothers' stories